Atomic-dispersed platinum anchored on porous alumina sheets as an efficient catalyst for diboration of alkynes. Issue 21 (14th February 2020) - Shang, Huishan; Chen, Wenxing; Jiang, Zhuoli; Zhou, Danni; Zhang, Jiatao
Abstract : An atomic-dispersed Pt catalyst (Pt/dp-Al2 O3 ) was fabricated via a simple wet impregnation method and demonstrated to be highly active and stable for the diboration of phenylacetylene, which is due to Pt/dp-Al2 O3 providing unique catalytic sites. Abstract : Atomic-dispersed Pt anchored on defect-rich porous alumina sheets (Pt/dp-Al2 O3 ) was accessed via a wet impregnation combined with pyrolysis method. These nanosheets functionalized by atomic-dispersed Pt possess a high density of active sites, exhibiting an exceptional catalytic activity combined with cyclic performance in the diboration of alkynes. The selectivity and conversion yield could reach as high as 97% and 98%, respectively.